The thermoluminescence response of doped SiO2 optical fibres subjected to photon and electron irradiations - Ramli, Ahmad Termizi (Elsevier B.V., 2009)
Ion beams are used in radiotherapy to deliver a more precise dose to the target volume while minimizing dose to the surrounding healthy tissue. For optimum dose monitoring in ion-beam therapy, it is essential to be able to measure the delivered dose with a sensitivity, spatial resolution and dynamic range that is sufficient to meet the demands of the various therapy situations. Optical fibres have been demonstrated by this group to show promising thermoluminescence properties with respect to photon, electron and proton irradiation. In particular, and also given the flexibility and small size of optical fibre cores, for example 125.0±0.1 μm for the Al- and Ge-doped fibres used in this study, these fibres have the potential to fulfill the above requirements. This study investigates the thermoluminescence dosimetric characteristics of variously doped SiO2 optical fibres irradiated with alpha particles from 241Am. Following subtraction of the gamma contribution from the above source, the thermoluminescence characteristics of variously doped SiO2 optical fibres have been compared with that of TLD-100 rods. The irradiations were performed in a bell jar. Of related potential significance is the effective atomic number, Zeff of the fibre, modifying measured dose from that deposited in tissues; in the present work, a scanning electron microscope and associated energy dispersive X-ray spectroscopy facility have been used to provide evaluation of Zeff. For Ge-doped fibres, the effective atomic numbers value was 11.4, the equivalent value for Al-doped fibres was 12.3. This paper further presents results on dose response and the glow curves obtained. The results obtained indicate there to be good potential for use of variously doped SiO2 optical fibres in measuring ion-beam doses in radiotherapeutic applications.